Forecast Accuracy of Individual Analysts in Nine Industries - O'Brien, Patricia C. (Journal of Accounting Research, 1990)
The purpose of this paper is to investigate whether financial analysts with superior earnings forecasting ability can be distinguished on the basis of ex post forecast accuracy. I explore the question by estimating and comparing average accuracy across individuals, and by considering whether the observed distribution of analyst forecast accuracies differs from the distribution expected if their relative performances each year were purely random. Overall, I do not find systematic differences in forecast accuracy across individuals. Financial press coverage suggests there are superior financial analysts. For example, Institutional Investor's annual All American Research Team includes analysts rated by money managers as superior on a variety of criteria, including earnings forecasting, ability to pick stocks, and the quality of written reports. Clearly, financial analyst services other than forecast accuracy are valued by their clients. I focus on only one activity, earnings forecasting, for two reasons. First, forecast data are available, quantitative, and can be evaluated against observable earnings outcomes. Services such as insightful, well-written research reports are harder to evaluate quantitatively. Second, academic use of analyst forecasts as earnings expectations data in capital markets empir-